2010
DOI: 10.1111/j.1439-0329.2010.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Current and future molecular approaches to investigate the white pine blister rust pathosystem

Abstract: Kim, M.-S.; and Klopfenstein, N. B., "Current and future molecular approaches to investigate the white pine blister rust pathosystem" (2010 SummaryMolecular genetics is proving to be especially useful for addressing a wide variety of research and management questions on the white pine blister rust pathosystem. White pine blister rust, caused by Cronartium ribicola, is an ideal model for studying biogeography, genetics, and evolution because: (1) it involves an introduced pathogen; (2) it includes multiple pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 121 publications
0
50
0
Order By: Relevance
“…Whether there are alpine and lowland biotypes or native and invasive rusts would require additional study. R ichardson et al. (2010); and see their Fig.…”
Section: Historical Biogeographymentioning
confidence: 94%
See 2 more Smart Citations
“…Whether there are alpine and lowland biotypes or native and invasive rusts would require additional study. R ichardson et al. (2010); and see their Fig.…”
Section: Historical Biogeographymentioning
confidence: 94%
“…R ichardson et al. (2009) presented preliminary results of a currently active but incomplete survey of the blister rusts of white pines (see R ichardson et al. 2010; : Fig.…”
Section: Taxonomy and Life Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…At the molecular level, a few studies revealed several Pinus gene families involved in defense response against C. ribicola infection. Plant R family of NBS-LRR proteins and multiple families of PR proteins, including chitinases (PR3), thaumatin like proteins (PR5), intracellular ribonuclease-like proteins (PR10), and anti-microbial peptides/proteins (AMPs), contributed in part to host resistance in the WPBR interactions [41,100].…”
Section: Genomic Selection Of Partial Resistancementioning
confidence: 99%
“…For example, the plant disease resistance (R) family of NBS-LRR proteins and several families of pathogenesis-related (PR) proteins, including chitinases (PR3), thaumatin like proteins -TLPs (PR5), intracellular ribonuclease-like proteins (PR10), and anti-microbial peptides/proteins (AMPs), have been shown to contribute to host resistance in WP-BR interactions [5,6]. A recent proteomic profiling uncovered over one hundred P. monticola proteins modulated by C. ribicola inoculation, which included heat shock proteins (HSPs), reactive oxygen species (ROS) scavenging enzymes, and intermediate factors functioning in the signal transduction pathways triggered by well-known plant R genes, as well as other defence-related proteins [7].…”
Section: Introductionmentioning
confidence: 99%